Nurses' perceptions of their foot health: implications for occupational health care. - Stolt M; Miikkola M; Suhonen R; Leino-Kilpi H (My University, 2022)
Nursing practice includes static standing and much walking causing strains to lower extremities. However, little is known about nurses’ foot health and particularly their perceptions of their foot health. Therefore, in this study operating room nurses’ perceptions of their foot health was investigated and promoting and hindering factors were identified. In total, 14 operating room nurses participated in in-depth interviews. The informants regarded foot health as part of general health and moreover a significant part of work well-being. Promoting factors for foot health were activity in sports and foot self-care as well as varying work conditions and seeing patients with severe foot conditions which served as a motivating factor to care for their own feet. On the contrary, hindering factors were unsuitable footwear, constant standing, and lack of motivation to care for their own feet. Based on this study, nurses’ value their foot health which should be promoted. Nurses could benefit from annual foot health assessments and foot self-care education provided by occupational health professionals.